2022
DOI: 10.1111/1440-1630.12821
|View full text |Cite
|
Sign up to set email alerts
|

‘I'm institutionalised … there's not much I can do’: Lived experience of housing related delayed discharge

Abstract: Introduction: Delayed discharge from inpatient mental health units is the continued hospitalisation of consumers after being assessed as ready to be discharged. This is common in adult inpatient mental health services and is usually due to a lack of appropriate housing for discharge. Research indicates a range of possible negative impacts, but no studies have explored consumers' perspectives on this issue. This study explores consumers' perspectives of the experience of housing related delayed discharge (HRDD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Most importantly, it is detrimental to the people affected. Our qualitative study of the perspectives of people experiencing HRDD from mental health units found that participants reported a pervasive lack of choice and control over ‘the basics in life’, ‘how I spend my time’, ‘who I spend time with’, and ‘my future’, resulting in reduced mental and physical well-being and anticipated difficulty transitioning back into the community (Chua et al, 2022 ). This lack of choice and control represents an infringement of consumers’ rights under the United Nations Convention on the Rights of Persons with Disabilities (United Nations, 2006 ), including their rights to: liberty (Article 14); choice of living situation and inclusion in the community (Article 19); and participation in all areas of life (Article 9).…”
mentioning
confidence: 99%
“…Most importantly, it is detrimental to the people affected. Our qualitative study of the perspectives of people experiencing HRDD from mental health units found that participants reported a pervasive lack of choice and control over ‘the basics in life’, ‘how I spend my time’, ‘who I spend time with’, and ‘my future’, resulting in reduced mental and physical well-being and anticipated difficulty transitioning back into the community (Chua et al, 2022 ). This lack of choice and control represents an infringement of consumers’ rights under the United Nations Convention on the Rights of Persons with Disabilities (United Nations, 2006 ), including their rights to: liberty (Article 14); choice of living situation and inclusion in the community (Article 19); and participation in all areas of life (Article 9).…”
mentioning
confidence: 99%